ANALISIS KEPEMILIKAN SENJATA API DINAS POLRI DAN IMPLIKASI PSIKOLOGIS TERHADAP PEMEGANGNYA DI POLRES PALU - Herfian, Herfian (Katalogis, 2015)
The objective of this research is to identify and analyze the Implementation of Firearms and the Psychological Implications to Firearms Holders in Palu Resort Police Department, Central Sulawesi Provincial Police Department. It is a qualitative research with 4 informants. The data was collected through interviews and documentations. The analysis techniques adopted comprised (1) Data Editing, (2) Data Grouping, (3) Data Interpretation and Conclusion and Recommendation. The results of the research showed that (1) the firearms abuse by police officers was due to failure to follow standards, mechanisms and procedures, (2) the measures taken to prevent firearms abuse by police officers were preventive through socialization of Police Regulation Number 8 Year 2009, and repressive to affect sanctions to any firearms abuser in attempt to prevent further abuse, and (3) the psychological implication to police officers was that it could enhance their (over confidence) in enforcing law in the field